Quantitative evaluation of UHF TV white spaces, for rural broadband connectivity - Madhumbu, Shariwa T. (Midlands State University, 2019)
With the increase in use of internet access across the world, there has been a shift from classic wired connection technology to the faster and efficient mobile wireless solutions. Zimbabwe as a country is also experiencing this upsurge. However, its hindered by the lack of flexible connection solutions in the densely populated rural areas. A perceived “digital divide” exists between the rural and urban population. This study seeks to explore a new way of breaking this divide by exploring into Television White Spaces, a relatively untouched technology which makes use of unused frequencies in the RF spectrum. White spaces will occur in the UHF band in Zimbabwe when the country completes its Digital Broadcast migration programme. This study seeks to use methodologies to realize these white spaces and enhance the coexistence for both incumbent and TVWS technologies in the band. This is to aide with the connectivity of the far-fetched rural areas that are traditionally out of reach using orthodox wireless technology.